Криозащитная эффективность комбинированной среды с непроникающим и проникающим криопротекторами при замораживании эритроцитарных суспензий различного объема - Ramazanov, Viktor V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
Osmotic properties of erythrocytes, frozen in suspesions with different volumes in combined medium with 15% dextran and 5% DMSO were studied. It was established that the increasing of sample volume subjected to freezing and reduction of freezing and thawing rate did not result in a significant rise of H+ ion flow and loss of membrane barrier function in respect of glutathione in cells washed free of cryopreservative. The obtained results allowed to suggest that freezing in combined medium independent on cooling rate provided optimal dehydration of cells. It was determined that inclusion of DMSO into a cryopreservative based on dextran and its penetration into cells decreased dehydration and hypertonic stress rate, stipulated by concentrating of non-penetrating components of medium during freezing. Lowering of hypertonic stress was a pre-condition of erythrocyte membrane resistance to post-hypertonic stress during freeze-thawing and contributed to preservation of osmotic properties of cells washed free of cryopreservative.